An investigation into the impact of cryogenic environment on mechanical stresses in FRP composites. (July 2015) - Fifo, O; Basu, B
Abstract: Fibre reinforced polymer (FRP) composites are fast becoming a highly utilised engineering material for high performance applications due to their light weight and high strength. Carbon fibre and other high strength fibres are commonly used in design of aerospace structures, wind turbine blades, etc. and potentially for propellant tanks of launch vehicles. For the aforementioned fields of application, stability of the material is essential over a wide range of temperature particularly for structures in hostile environments. Many studies have been conducted, experimentally, over the last decade to investigate the mechanical behaviour of FRP materials at varying subzero temperature. Likewise, tests on aging and cycling effect (room to low temperature) on the mechanical response of FRP have been reported. However, a relatively lesser focused area has been the mechanical behaviour of FRP composites under cryogenic environment. This article reports a finite element method of investigating the changes in the mechanical characteristics of an FRP material when temperature based analysis falls below zero. The simulated tests are carried out using a finite element package with close material properties used in the cited literatures. Tensile test was conducted and the results indicate that the mechanical responses agree with those reported in the literature sited.